Aids and mental health: bibliographical review - Carvalho, Carolina Maria L.; Braga, Violante Augusta B.; Galvão, Marli Teresinha G. (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Introduction: the aids marks the infected person deeply because it affects his physical, mental and social wellbeing and involves negative feelingssuch as depression, anguish and fear of death, interfering in his identity and selfesteem. The HIV bearers who use psychiatric services, face difficulties to receive appropriate assistance to the treatment of aids. This way, we recognized the need to investigate about the attention in health that isbeing given to these patients, taking into account that the complexity of this pathological situation generates demands of every order and a multipleapproach. Objective: to present a bibliographical review contextualizing the HIV-aids subjects related to mental health. Methods: it is a bibliographical investigation, of qualitative analysis of the researched content. Articles of indexed journals were captured, in the period from 1980 to 2004,corresponding from the discovery of the disease to the present days, with the intention of obtaining publications about aids that contextualized themental health. For obtaining the articles the LILACS index was used. Results: we noticed that the patients from the mental health services belong to apopulation with a high vulnerability degree to STD and HIV-aids, being common among these people a distortion of the perception in relation to theinfection risk, besides the difficulty with adoption of preventive measures and with access to the treatment when already infected. Conclusion: this bibliographical revision shows the lack of studies on the theme, raising the need and urgency of rethinking of the relationship between STD/HIV-aidsand the attention in mental health.